2011
DOI: 10.4049/jimmunol.1003937
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Thresholds for Naive CD8+ CTL Activation by Peptides and Engineered Influenza A Viruses

Abstract: High-avidity interactions between TCRs and peptide + class I MHC (pMHCI) epitopes drive CTL activation and expansion. Intriguing questions remain concerning the constraints determining optimal TCR/pMHCI binding. The present analysis uses the TCR transgenic OT-I model to assess how varying profiles of TCR/pMHCI avidity influence naive CTL proliferation and the acquisition of effector function following exposure to the cognate H-2Kb/OVA257–264 (SIINFEKL) epitope and to mutants provided as peptide or in engineere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Therefore, in order to directly test whether increased TCR stimulation resulted in similar increases in LAG3, we employed previously reported variants of the SIINFEKL peptide, SIIGFEKL, and EIINFEKL, which have been demonstrated to bind H-2k b with similar affinity but have decreased affinity for the OT1 TCR. 42 Consistent with our expectations, stimulation of naive OT1 splenocytes with the epitopte variants led to a decrease in LAG3 on CD8…”
Section: Cd4-cd8supporting
confidence: 89%
“…Therefore, in order to directly test whether increased TCR stimulation resulted in similar increases in LAG3, we employed previously reported variants of the SIINFEKL peptide, SIIGFEKL, and EIINFEKL, which have been demonstrated to bind H-2k b with similar affinity but have decreased affinity for the OT1 TCR. 42 Consistent with our expectations, stimulation of naive OT1 splenocytes with the epitopte variants led to a decrease in LAG3 on CD8…”
Section: Cd4-cd8supporting
confidence: 89%
“…By simulating comparable conditions and modes of antigen presentation to Des and OT-I T cells, we confirmed that, regardless of expression levels and frequency of transduction, H-2K b expression did not promote Des T-cell effector function, whereas OVA expression induced OT-I CTL differentiation. Our results suggest that these differing outcomes might be a result of different strengths of TCR:pMHC interactions, a factor known to be critical to the outcome of T-cell responses in the periphery (22,32). Although the relative affinities of the Des and OT-I TCRs for their respective ligands are not known, Des T cells are less efficiently retained and require a longer time before undergoing first division after antigen encounter compared with OT-I cells, suggesting that Des TCR affinity for H-2K b :KVITFIDL is lower than OT-I TCR affinity for H-2K b :SIINFEKL.…”
Section: Discussionmentioning
confidence: 85%
“…T cell avidity is driven primarily by TCR affinity for its cognate peptide (Corse et al, 2011; Denton et al, 2011; Gourley et al, 2004), and also expression levels of CD3/TCR complex and adhesion molecules. We determined that high and low avidity clones expressed CD3/TCR at similar levels (data not shown).…”
Section: Resultsmentioning
confidence: 99%